Game engines ray-tracing models for indoor channel modeling - Cardona, Narcis; Guevara, Dinael; Navarro Cadavid, Andres (IEEE, 2014)
This paper investigates the use of a full 3D ray-tracing system based on Game Engine for the prediction of channel parameters in indoor using frequencies lower than usual. We explore the modeling of indoor channel for Digital TV frequencies and analyze the behavior of material on such low frequencies and how the frequencies affect the constitutive parameters of materials in the scenario. Because of the environment used for experimentation, the number of rays is very high and the number of interactions is higher than usual. We show results of the ray tracing model compared with measurements of delay spread at 594MHz.
Keywords: Modelado; Conductividad; Rayos; 3D; Ingeniería de sistemas y comunicaciones; Systems engineering; Telecomunicaciones